A comparison of reading comprehension across paper, computer screens, and tablets: Does tablet familiarity matter? - Guang Chen; Wei Cheng; Ting-Wen Chang; Xiaoxia Zheng; Ronghuai Huang (Journal of Computational Education, 2014)
Nowadays, reading on screens is an essential part of our daily life. Tablet computers, with great portability, usability, and interactivity, have become a popular mobile device for learning and reading. However, there were few studies to explore the effects on reading using tablet computers, and the difference between computer-based reading and paper-based reading is still not clear. Therefore, this study focused on to investigate the effects of reading comprehension across paper, tablets, and computers. Moreover, the user familiarity was regarded as a potential issue to affect the reading on digital devices. Accordingly, this study took into account to figure out the effects and impacts of the user familiarity on reading comprehension while reading on tablets. Two question types of reading comprehension, multiple choice questions as the shallow level comprehension and summarization as deep level comprehension, were considered to test the reading comprehension. Data from 90 college students were used in the data analysis. It was indicated that the paper group performed significantly better than the computerbased reading on the shallow level comprehension. This finding confirmed and eliminated the factors of reading in paper and computer for the previous studies. For example, the way of navigation was still the main reason to affect the process of reading. However, the switch between the reading and test media was not the reason to affect the reading comprehension. In order to figure out why there was no difference between tablets and the other two media platforms, the tablet familiarity was evaluated to find out whether the familiarity affect reading comprehension or not. The result showed that the high level of tablet familiarity group performed significantly better than low level group on deep level comprehension. For this result, it could conclude that if providing students enough and appropriate training, they could have higher familiarity with tablets and then gain better reading comprehension using tablets.   Keywords :  Screen reading, Digital reading, Reading comprehension, Tablet familiarity
Keywords: compréhension; lecture à l'écran; lecture numérique